Value Relevance of Earnings Component in the Financial Industry - Yulianti, Retno; Zuhrohtun, Zuhrohtun (RSF Conference Series: Business, Management and Social Sciences, 2021)
PSAK No. 1 of 2009 is enforced from 2011 onwards. The presentation of the income statement changes to a comprehensive income statement consisting of operating income, non-operating income, net income, other comprehensive income (OCI). The purpose of this study was to test the value relevance of OCI and other components of earnings that were tested based on the relationship between OCI and stock prices in the financial industry. The population in this study are all companies listed on the Indonesia Stock Exchange which are included in the financial industry in 2016-2019. Based on the determination of the sample using the purposive sampling method, the research sample obtained was 335 firm years. The data is processed using OLS regression. This study indicates that OCI, non-operating income, and comprehensive income have value relevance which is indicated by the negative effect of OCI on stock prices and the positive effect of non-operating income and comprehensive income on stock prices. However, operating income and net income have no effect on stock prices.